Plasmonic Properties of Colloidal Assemblies - Rossner, Christian; Koenig, Tobias A. F.; Fery, Andreas (Advanced Optical Materials, 2021)
The assembly of metal nanoparticles into supracolloidal structures unlocks optical features, which can go beyond synergistic combinations of the properties of their primary building units. This is due to inter-particle plasmonic coupling effects, which give rise to emergent properties. The motivation for this progress report is twofold: First, it is described how simulation approaches can be used to predict and understand the optical properties of supracolloidal metal clusters. These simulations may form the basis for the rational design of plasmonic assembly architectures, based on the desired functional cluster properties, and they may also spark novel material designs. Second, selected scalable state-of-the-art preparative strategies based on synthetic polymers to guide the supracolloidal assembly are discussed. These routes also allow for equipping the assembly structures with adaptive properties, which in turn enables (inter-)active control over the cluster optical properties.
CRIS-Team Scopus Importer:2022-04-14
Keywords: electromagnetic simulations; nanomaterial synthesis; plasmonics; self-assembly; supracolloidal